Critical illness polyneuromyopathy - a well-known but still controversial entity - Bednařík, Josef; Vondráček, Petr (Scripta medica Facultatis medicae Universitatis Brunensis Masarykianae, 2009)
Two main clinical, pathological and electrophysiological types of acquired neuromuscular involvement in critically ill patients have been described in the past two decades: critical illness polyneuropathy and critical illness myopathy. However, there, still exist many controversies and unresolved questions regarding definition, terminology, diagnosis, and differentiation of what appears to be a spectrum of more or less overlapping neuromuscular disorders rather than distinct entities, and recently a new term – critical illness polyneuromyopathy (CIPM) has been coined. CIPM may present with muscle weakness and failure to wean from mechanical ventilation, but is discovered more often and earlier by electrophysiological examination. In this review, the incidence, clinical, electrophysiological and histopathological features, and risk factors of CIPM will be described. Among the most important risk factors for CIPM are sepsis or systemic inflammatory response syndrome and the severity of multi-organ failure. Acquired neuromuscular weakness in critically ill patients should be regarded as a part rather than a complication of critical illness – dysfunction or failure of a further (neuromuscular) system.
Keywords: jednotky intenzivní péče; diferenciální diagnóza; Diagnostic Techniques, Neurological; kritický stav; Microscopy, Electron; myasthenia gravis; Electrophysiology; biopsie; Muscular Diseases; nemoci svalů; Neuromuscular Diseases; polyneuropatie; neuromuskulární nemoci; diagnostické techniky neurologické; lidé; Intensive Care Units; Myasthenia Gravis; elektronová mikroskopie; Diagnosis, Differential; Polyneuropathies; Biopsy; Guillainův-Barrého syndrom; Muscle Weakness; svalová slabost; elektrofyziologie; Guillain-Barre Syndrome; Critical Illness; Humans